Manager's Perception of the Modern Marketing Concept and its Applications in the Libyan Industrial Organizations: A Field Re search of the Public Libyan Industrial Organizations in Benghazi - الدراجي, مرعي; الكيخيا , فيصل (Dirasat in Economics and Business, 2019)
The aim of this research is to determine the manager's Perception levels of the modern marketing concept, in terms of its nature, applications, the importance of its application, and whether this perception is reflected as the actual practice applied in the various marketing activities in the organizations that undergo, in this research. The society of the research include all senior and middle management of departments of the public Libyan industrial organizations operating in Benghazi city. The survey was used with two indicators, qualitative and quantitative; contain several indicators, which would achieve the objectives of the research. The most significant results of the research according to each indicator that, there is a lack in the manager's perception of the modern marketing concept in the organizations in this research, revealed a sizable lack in manager's perception of the importance of applying the concept. The modernize applications were not reflected enough on marketing practices to apply the concept, motivators and reasons for applying the modern marketing concept were high. The research also found that there is a significant lack of the necessary requirements as factors needed to modernize marketing in the organizations under the research, The obstacles to modernize marketing in the organizations in the research reached 73%, the Weighted Arithmetic Mean was medium at (2.69). According to these results, the research presented a set of implications and recommendations that management of organizations should focus on.